The researching of the facing stone cutting with the diamond wire - Башинський, Сергій Іванович (Technology audit and production reserves, 2013)
The diamond wire cutting is still little-investigated despite the high level of the resource-saving and the popularity. This can be explained by the complication in experimenting with the quarry wire saw machines. There was paned the experiment with the stationary diamond wire machine. The developed method of testing allows repeat the experiment for the different types of the rock with the necessary number of cases. There was found out the dependence between the wrapping angle of the nature stone block with the diamond wire and the power parameters of cutting. Also there were found out the numerical value and the law of variation of the diamond cutting coefficient. It has significance for the theory of the diamond wire cutting. The assumption about dependence between power and force parameters of the dimension stone cutting with the diamond wire was confirmed with the results of the researching. The results have the correcting character for the basic foundation of the diamond wire cutting.